Development of Media Authoring Tools to Improve Learning Outcomes in Mathematics Class V Elementary School - Purwanti, Eni; Firdaus, Rangga; Sutiarso, Sugeng; Herpratiwi, Herpratiwi (UNDIKMA, 2024)
Education is an important aspect in the development of a nation, with the main goal of the Indonesian government to complete 9 years of Basic Education. One of the efforts to improve the quality of education is through the development of media authoring tools in learning mathematics in elementary schools. This research aims to create interactive learning media that can help grade V students understand mathematics concepts better. By using authoring tools, teachers can create interesting learning materials and make it easier for students to learn. The graduate competency standards set by the government are also a reference in the development of this media. It is expected that through the use of authoring tools, students' mathematics learning outcomes can improve significantly